Pengaruh Moralitas Individu, Religiusitas dan Pengendalian Internal Terhadap Kecenderungan Kecurangan (Fraud) Pada Lembaga Perkreditan Desa (Lpd) Di Kecamatan Tabanan - Yasa, I Gede Reza Wiadnyana; Sumadi, Ni Komang; Muliati, Ni Ketut (Hita Akuntansi dan Keuangan, 2024)
Misrepresentation (extortion) is a slip-up made purposefully, in the extent of bookkeeping, the idea of misrepresentation (extortion) is a deviation from bookkeeping systems that ought to be applied in a substance. Accounting fraud (also known as fraud) is committed by both internal and external parties of the company, as well as by factors that influence it. The company should provide sufficient confidence in the achievement of the company's goals and its survival. The reason for this study is to decide the impact of individual ethical quality, legalism and inner control on the propensity of bookkeeping misrepresentation (Extortion). This exploration was led on LPDs in Tabanan Locale, Tabanan Rule, with a complete example of 82 individuals. The saturated sampling method was used to select the sample, and descriptive statistics, the validity and reliability tests, the classical assumption test, the multiple linear regression analysis, the coefficient of determination (R2), the F test, and the t test were used for data analysis. The findings revealed: 1) individual profound quality affects the variable of the propensity of misrepresentation (extortion). ( 2) Legalism affects factors of misrepresentation propensities (extortion). ( 3) Factors associated with fraud tendencies are negatively impacted by internal control.